Koagulasi Protein Pada Pembuatan Tahu pengan Menggunakan Enzim Papain - Ayu Ardia Rizki; Faridah -; Elwina - (Jurnal Teknologi, 2017)
Enzymes are protein which are used as catalyst in biologycal systems and could lead to changes of certain reactions. One of the enzymes that can be used to hydrolyze the proteins is papain enzyme. This study aimed to determine the effect on the reaction kinetics combine with   the addition of the papain enzyme from papaya latex extraction. The soy milk obtained from the extraction of soya in a was of soybeans that have been soaked ± 12 hours and then cleaned and blended with the addition of hot water for three times. The ratio of weight of soya beans  to water is 1 : 3. Further more, the soy milk was then heated and coagulated at 70oC and added with concentration of the papain enzyme from papaya latex extraction of 200,  600, and 1000 ppm concentration. The test results of reaction kinetics are obtained by Km 25 and Vm 3.303 ppm/minute.